Tahlīlu Tadriīsi Mahārah al-Kalām fā al-Kitāb al-Madrasī “Durūs al-Lughah al-‘Arabīyah ‘alā al-Thorīqah al-Hadīṡah fī al-Juz al-Awwal li al-Imam az-Zarkasyī wa al-Imām asy-Syubbnī” - Mahfiyah, Mahfiyah (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
Teaching Arabic by using books is pretty much a routines done by teachers and students in an institute or school. This study focuses on how to analyze the book Lessons of the Arabic Language on the Up-to-date method of teaching from the cultural, social, psychological, linguistic, and educational aspects and to identify the shortcomings and advantages of the teaching of Arabic by using books. This study employed qualitative descriptive research. The data were collected through observation and document analysis. The results of this study indicate that in terms of preparing the textbooks, one must consider such aspects as; the cultural, social, psychological, linguistic, and educational aspects. Moreover, even though it has some disadvantages, it does not diminish the quality of the book used in which it is evidenced on how popular method is implemented.